A Survey of Some Medicinally Important Plants in Villupuram District of Tamil Nadu India - Jagatheeswari, D (International Journal of Pharmaceutical & Biological Archive, 2012)
A Survey of Some Medicinally Important Plants in Villupuram District of Tamil Nadu India